PECULIARITIES OF METALLOGRAPHIC RESEARCHES OF STRUCTURE OF CAST METAL FROM WASTE OF HIGH-SPEED STEEL P6M5 - A. L. Valko; P. I. Papkovsky; S. P. Rudenko; L. R. Dudetskaya (Литьë и металлургия, 2014)
Techniques metallographic researches of structure and definition of size of grain of tool steels are offered. The structure of the fast-cutting steel received by a method electroslag remelting from a waste of tool manufacture is investigated.